Diabetic Foot Exercises for Hyperglycemia in Diabetes Mellitus Patient: A Case-Study - Sari, Elia Nanda Wulan; Dianita, Eka Mei; Nahariani, Pepin; Yulianto, Heri (Al-Hijrah Indonesia, 2024)
Background: Diabetes Mellitus is a metabolic disease characterized by increased blood sugar levels which occurs because the pancreas is unable to secrete insulin. Symptoms of diabetes mellitus cases are increased blood glucose levels, one action to overcome this is diabetes foot exercises. Objective: To determine the effectiveness of diabetes mellitus foot exercises in reducing blood glucose levels. Methods: Descriptive with presentation of case studies using a nursing care approach, namely assessment, diagnosis, intervention, implementation and nursing evaluation. Results: After carrying out nursing actions for 3 x 24 hours, it was found that blood glucose levels had decreased as evidenced by subjective data: the patient said that the weakness and tingling in the legs had decreased, objective data: decreased weakness, GDA examination was 129 mg/dL. Conclusions: There was a decrease in blood sugar levels after diabetes mellitus foot exercise. There are differences in the development of decreased blood glucose levels in patients with diabetes mellitus before and after the application of diabetes mellitus foot exercise.